Effectiveness of centralized procurement systems in public sector enterprises of Bangladesh : a focus on Economic Census 2013 - Islam, Md. Taslimul (BRAC University, 2016)
This dissertation report is submitted in partial fulfillment of the requirements for the degree of Masters in Procurement and Supply Management, 2014.